Labor Market Impacts and Effectiveness of Skills Development Programs in 5 States in India : Assam, Andhra Pradesh, Madhya Pradesh, Odisha, and Rajasthan - World Bank (Washington, DC, 2015)
Over the past few years, the Government of India (GOI) has been implementing five large national skills development (SD) programs to improve the employment and earnings prospects of urban and rural youth. The critical questions to be addressed are: what have been the employment outcomes of those programs?; what earnings premium do one give to trainees?; do program benefits justify the significant public investments made into them?; what organizational aspects affect delivery and reach?; and finally, based on these findings, what should be the course of action? This paper tries to address these questions, using data from a set of surveys of trainees (past and current), non-trainees (comparison group), employers, and training providers. The quantitative analysis has been complemented by a qualitative study based on interviews and focus group discussions, with focus on business processes, program management, and monitoring and evaluation (M and E). Five states have been taken into consideration for this analysis: Assam, Andhra Pradesh (AP), Madhya Pradesh (MP), Odisha, and Rajasthan. This paper comprises several sections. The first section provides introduction. Section two presents skills development programs; section three presents employment outcomes of SD programs; section four presents wage and earnings effects of SD programs; section five is cost-effectiveness of SD programs; section six is India versus international experience; section seven presents findings from the qualitative study; and section eight gives conclusions and policy recommendations.